Diagnostic value of the Wayne index in thyroid enlargement patients at Sultan Agung Islamic Hospital - Nur Anna Chalimah Sadyah; Tjatur Sembodo; Satyagraha, Muhammad Thifan; Silpa Ijmilani (Journal of the Pakistan Medical Association, 2025)
Hyperthyroidism, a prevalent metabolic disorder, poses diagnostic challenges due to variability in clinical presentations and access to laboratory tests. Given the clinical importance of hyperthyroidism and the challenges associated with timely and accessible laboratory testing for thyroid hormones, the evaluation of diagnostic tools, such as the Wayne index, is crucial. The current cross-sectional study, conducted from January to December 2022, evaluated the diagnostic performance of the Wayne index in detecting hyperthyroidism in 65 thyroid enlargement patients at the Sultan Agung Islamic Hospital, Indonesia. The Wayne index was assessed against thyroid stimulating hormone, free thyroxine, and total triiodothyronine. Sensitivity, specificity, predictive values, likelihood ratios, and area under the curve were calculated. Results showed sensitivity ranging from 86.1% to 92.6% and specificity from 66.7% to 79.3% for the Wayne Index across thyroid function tests, with an area under the curve ranging from 0.80 to 0.83. These findings suggested that the Wayne Index could serve as a reliable diagnostic tool for hyperthyroidism in clinical practice. Key Words: Hyperthyroidism, Wayne index, Diagnostic accuracy, Thyroid hormones.